2016
DOI: 10.1063/1.4958604
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of valve stiction based on normality test and Hammerstein system identification

Abstract: Thermodynamic analysis of the effect of reservoir temperature change on the performance of organic rankine cycle system on geothermal power plant AIP Conference Proceedings 1755, 110005 (2016) Abstract. The presence of static friction or stiction in a valve can lead to poor performance in industrial automation and control system. This paper presents a method to detect and quantify stiction based on normality test and Hammerstein system identification. Detection and quantification are showed by the and paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…A bootstrap Hammerstein system identification procedure was developed by Yan et al 31 to derive control limits for stiction parameters. Hutabarat et al 32 claimed that the cause of control loop oscillations can be found to be either external oscillatory disturbances or poor controller tuning if PV is normally distributed. The authors (Hutabarat et al 32 ) used the Hammerstein system based approach to detect and quantify stiction if PV is not normally distributed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A bootstrap Hammerstein system identification procedure was developed by Yan et al 31 to derive control limits for stiction parameters. Hutabarat et al 32 claimed that the cause of control loop oscillations can be found to be either external oscillatory disturbances or poor controller tuning if PV is normally distributed. The authors (Hutabarat et al 32 ) used the Hammerstein system based approach to detect and quantify stiction if PV is not normally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Hutabarat et al 32 claimed that the cause of control loop oscillations can be found to be either external oscillatory disturbances or poor controller tuning if PV is normally distributed. The authors (Hutabarat et al 32 ) used the Hammerstein system based approach to detect and quantify stiction if PV is not normally distributed. In all the Hammerstein model based methods discussed so far, the sticky valve was modeled by a data-driven model which was derived based on the input−output behavior shown in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
“…The Hammerstein methodology is used as a model framework and a two-stage optimization is used to identify model parameters. Hutabarat et al (2016) developed a stiction quantification method using a normality test followed by Hammerstein model methodology. First, a PV normality test is performed to find out whether the process is normally distributed on the basis of skewness and kurtosis values of PV data.…”
Section: Hammerstein Model-based Methodsmentioning
confidence: 99%
“…Hutabarat dkk. [8] melakukan pengembangan metode deteksi dan kuantifikasi friksi statik pada katup kontrol berbasis uji normalitas dan identifikasi sistem Hammerstein. Penelitian ini melakukan uji normalitas pada data PV lalu melakukan deteksi dan kuantifikasi friksi statik menggunakan pemodelan Hammerstein.…”
Section: Pendahuluanunclassified